UPAYA PENINGKATAN KEMAMPUAN MEMBACA DINI MURID TK MELALUI METODE CANTOL ROUDHOH - Aeni Latifah; Mariana Panji Ramadan (Jurnal El-Audi, 2022)
In childhood, you cannot really learn words, your skills develop rapidly, and in childhood you begin to understand and understand the meaning of words and what adults say one by one. Children can not only communicate with adults, but also with their peers. It is one of the preparations for kindergarten children to read simple words and know how to write and the meaning of words. Reading from an early age can have a positive impact on children's language development for the next level of education. Early reading is reading that is taught in the program to preschool children. The purpose of this study was to determine the early reading ability of children in the experimental group and the control group at Kartini 3 Nagrak Sukabumi Kindergarten and the implementation of early reading skills. Children through cantol roudhoh as well as supporting factors and inhibiting the implementation of children's early reading skills through cantol roudhoh. This study uses a quantitative approach, the method used is a quasi-experimental method. This research shows that there is a significant effect on the use of the cantol roudhoh method in early reading learning at TK Kartini 3 Nagrak. This is evident from the increased early reading ability of children before and after treatment. In other words, the use of the cantol roudhoh method is effective and can improve children's early reading skills.